Ultrananocrystalline diamond decoration on to the single wall carbon nano tubes - Sinha, B.; Late, D.; Jejurikar, S.M. (Applied Surface Science, 2017)
We have demonstrated the decoration of the ultrananocrystalline diamonds on single walled carbon nanotubes using a hot filament assisted chemical vapor deposition. Study reveals the critical influence of the filament to substrate distance on the formation of ultrananocrystalline diamonds on to the single walled carbon nanotubes. It is also observed that etching of carbon nanotubes, due to the presence of unavoidable atomic hydrogen throughout the chemical vapor deposition processes, can be significantly reduced by adjusting the filament to substrate distance. Morphological and structural investigations performed using high resolution transmission electron microscope suggests the growth of ultrananocrystalline diamond is subsequent to the formation of crystalline sp2 carbon layer on the nanotube wall, enabling us to suggest a growth model. The composite synthesized can be thought not only to use as a fuel cell catalyst support but also as chemical sensors, bio-sensors and micro electromechanical systems (MEMS).
Keywords: Carbon nanotubes; Composite Coating; Electron microscopy (STEM; Nanostructures; TEM and SEM)